Analisis Yuridis Penyelesaian Sengketa Konsumen Berdasarkan Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen - Sutrisno Hadi Nasution; Tri Reni Novita (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2026)
Legal protection for consumers is an important instrument for realizing legal certainty, justice, and a balanced relationship between consumers and business actors. Law Number 8 of 1999 concerning Consumer Protection provides the legal foundation for guaranteeing consumer rights and establishing litigation and non-litigation dispute resolution mechanisms. This study aims to analyze consumer legal protection under Law Number 8 of 1999, the consumer dispute resolution mechanism at the Lembaga Pembela Konsumen Negeri (LPKN), as well as the obstacles encountered and efforts to resolve them. This study employs normative legal research with a descriptive-analytical approach through statutory, conceptual, and case approaches. Primary, secondary, and tertiary legal materials were obtained through library research and analyzed qualitatively. The results show that Law Number 8 of 1999 has normatively provided legal protection by regulating the rights and obligations of consumers and business actors, as well as dispute resolution mechanisms. In the case examined, LPKN carried out its advocacy and legal assistance functions through litigation. However, the lawsuit was declared inadmissible due to formal defects and an inaccurate construction of the legal basis. The effectiveness of consumer protection remains constrained by issues concerning legal standing, formalistic judicial approaches, low legal awareness, and institutional limitations. Therefore, stronger regulations, legal harmonization, increased institutional capacity, and improved public legal education are necessary to establish a more effective and equitable consumer protection system that provides legal certainty.